ANALYSIS OF QUESTIONNAIRE RESULTS ON POSTURE STATUS IN PRIMARY SCHOOL STUDENTS AND THE FACTORS AFFECTING IT - qizi, Narmamatova Sabina G‘ayrat; yo‘nalishi, metodikasi; magistranti, 1-kurs (Research Focus International Scientific Journal, 2026)
This article examines posture status in primary school students and the main factors affecting it. As part of the study, a questionnaire was conducted with the participation of 40 respondents, and their daily activities, level of physical activity, hygienic habits, and status in the educational process were analyzed. The results showed that factors such as inactivity, incorrect sitting habits, heavy school bags, unsuitable school furniture, and insufficient physical activity affect students’ posture status. Some students also reported symptoms such as fatigue and pain in the back and lower back muscles. The results of the study scientifically demonstrate the need to properly form posture and strengthen preventive measures in primary school students.